Peran Oikumene Dalam Misi Gereja Untuk Perdamaian Dan Keadilan Sosial - Marco Menang Iman P Padang; Meditatio Situmorang (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
The ecumenical movement seeks to unite churches divided in denomination, doctrine, and practice, while fighting for peace and social justice. This article reviews the history, theological foundations, and application of ecumenism in the church's mission. This movement was born from the need for Christian unity, realized in Indonesia through the formation of the Fellowship of Churches in Indonesia (PGI) to strengthen cross-denominational fellowship. Its theological foundation is poured into Jesus' prayer for unity and the Great Commission. In addition to unity, ecumenism supports social justice as a manifestation of Christ's love. The main challenges include doctrinal differences, leader-congregation disputes, cultural differences, and political pressure. Inclusive ecumenical education and congregational participation are the keys to realizing church unity in facing pluralism and social challenges.